APPLICATION OF AUDIO VISUAL LEARNING MEDIA TO IMPROVING EARLY CHILDHOOD LEARNING OUTCOMES - Khairatun Nisa (Sean Institute, 2023)
This study aimed to determine the effect of audio-visual media-based learning on early childhood learning outcomes. Due to situations that require the use of technology in learning and the demands of teaching and learning activities that are increasingly developing to keep up with the times. Educators are expected to be able to utilize learning media as a support for teaching and learning activities to create interactive learning for students so as to increase students' understanding of receiving learning which will affect learning outcomes. The method used in this activity is the direct method, in which the team directly provides training to teachers, and the teacher then carries out learning activities using audio-visual media. The results achieved from this program by implementing audio-visual learning videos can help schools, teachers, and children improve children's learning outcomes at Harapan Bangsa Gemilang PAUD.